An Overview of Gut Microbiota and Colon Diseases with a Focus on Adenomatous Colon Polyps - Pop, Oana Lelia (Int J Mol Sci, 2020)
It is known and accepted that the gut microbiota composition of an organism has an impact on its health. Many studies deal with this topic, the majority discussing gastrointestinal health. Adenomatous colon polyps have a high prevalence as colon cancer precursors, but in many cases, they are hard to diagnose in their early stages. Gut microbiota composition correlated with the presence of adenomatous colon polyps may be a noninvasive and efficient tool for diagnosis with a high impact on human wellbeing and favorable health care costs. This review is meant to analyze the gut microbiota correlated with the presence of adenomatous colon polyps as the first step for early diagnosis, prophylaxis, and treatment.